Periappendicitis in children and its clinical significance - Özel, Ş. Kerem; Kazez, Ahmet; Köseo?ullari, A. Aysel; Özercan, Ibrahim H. (My University, 2004)
Aim: The aim of this study is to evaluate the appendectomy materials of the children with the diagnosis of periappendicitis who have been operated for acute abdomen. Method: The reports of 13 children treated in our clinics between February 1998 and March 2003 have been reviewed retrospectively. These cases were evaluated according to their age, gender, presence of fever, associated symptoms, pain duration and location, physical examination of the abdomen, serum leucocyte counts, ultrasonography and X-ray findings, preoperative diagnosis and operative findings. Results: A total of 6 girls and 7 boys with ages between 3 and 12 (5.2±3 years) were evaluated. Associated pathologies to periappendicitis were acute appendicitis in 5 patients, adhesive bowel obstruction in two, primary peritonitis, intussusception, Salmonellosis, pelvic inflammatory disease, torsion of ovarian teratoma and blunt abdominal trauma in one patient each. Hyperemia, edema and increase of vascularity were present in the appendix of all patients. They were diagnosed as periappendicitis histopathologically. Peritoneal irritation was present in all cases. Leucocytosis was present in 10 patients (77%), and fever was present in 5 patients (38%). Conclusion: Periappendicitis can be seen in cases where appendix is influenced by the pathologies causing peritoneal irritation as well. The need for appendectomy in cases diagnosed as periappendicitis peroperatively is debatable. Whether periappendicitis is a clinical entity or a pathological finding is the question that needs to be answered. Unless the opposite is proven, appendectomy is still the ideal approach for periappendicitis.
Çocuklarda periapandisit ve klinik önemi
Keywords: Appendicitis; Periappendicitis